Pluronic F127 "nanoarmor" for stabilization of Cowpea mosaic virus immunotherapy - Matthew D. Shin; Eunkyeong Jung; Miguel A. Moreno‐Gonzalez; Oscar A. Ortega‐Rivera; Nicole F. Steinmetz (Wiley, 2024)
Abstract Our lab demonstrated that intratumoral Cowpea mosaic virus (CPMV) is a potent antitumor immunotherapy when used as in situ vaccine. As we pave the way for human clinical translation, formulation chemistry needs to be optimized for long‐term storage of the drug candidate. In this work, CPMV was nanoengineered with Pluronic F127 to realize liquid and gel formulations which mitigate structural changes and RNA release during long‐term storage. We evaluated the CPMV‐F127 formulations for their stability and biological activity through a combination of in vitro assays and efficacy in vivo using a B16F10 murine melanoma model. Results demonstrate that both F127 liquid and gel formulations preserve CPMV structure and function following extended periods of thermal incubation at 4°C, 25°C, and 37°C. Heat‐incubated CPMV without formulation resulted in structural changes and inferior in vivo efficacy. In stark contrast, in vivo efficacy was preserved when CPMV was formulated and protected with the F127 "nanoarmor."